Harnessing organoid technology in urological cancer: advances and applications in urinary system tumors - Xiaoting Wang; Danyan Lin; Ninghan Feng (World Journal of Surgical Oncology)
Abstract The organoid approach preserves the intricate molecular and genetic characteristics of tumor tissues, playing a pivotal role in advancing precision oncology. This preservation enables the exploration of cancer therapies and in vitro validation of drug efficacy. Organoids have emerged as indispensable tools in the study of urological cancers, facilitating research on tumorigenesis, drug testing, and the development of therapeutic combinations. Their superiority over traditional 2D cell cultures and patient-derived xenograft (PDX) models lies in their enhanced ability to more accurately replicate the in vivo environment. Modern organoid platforms integrate 3D bioprinting, co-culture systems, microfluidics, and artificial intelligence to significantly improve the precision, scalability, and efficiency of cancer research. These integrated systems serve as powerful analytical tools, propelling the development of personalized therapies for urological malignancies. This article provides a comprehensive review of the establishment and potential of organoid technologies in treating the three major urogenital system cancers—prostate, bladder, and renal—highlighting their trajectory from basic research to clinical applications and their expanding synergy with bioengineering innovations. Graphical Abstract Organoids serve as a bridge between preclinical models and personalized therapies, providing a key preclinical model for addressing urological tumors.